Real Estate M&A - García Long, Sergio (2023)
This paper is a brief mapping of the contractual aspects involved in real estate M&A (mergers and acquisitions) transactions. For this purpose, it focuses on certain contractual categories (especially legal transplants) and on the legal discussions of transactional practice.